The handy accounting answer book - Gray, Amber (Accountant) (Visible Ink Press, 2019)
Presents lessons on money management and financial responsibility through use of accounting of one's money, savings, investments, bills, interest rates, and taxes. Offers answers on accounting terms, functions and fundamental concepts.